Establishment of Minimum Acceptance Criterion for Strand Bond as Measured by ASTM A1081 - Riding, Kyle A.; Peterman, Robert J.; Polydorou, Thomaida (My University, 2016)
ASTM International recently adopted ASTM A1081, Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand, a pull-out test procedure to verify steel strands' ability to bond to cementitious materials before they are used as tensile reinforcement in pretensioned concrete members. PCI commissioned a study to determine a minimum ASTM A1081 bond threshold value for steel strand to be used in pretensioned applications. The minimum acceptance criteria for ASTM 1081 were determined by comparing ASTM A1081 pull-out strengths for three strands of different bond characteristics to their performance in pretensioned beams as measured by transfer lengths and moment capacity when loaded at a point at 60% or 80% of the ACI 318-14 calculated development length from the beam end. Statistical analysis of the fl xural beam testing data and correlation with the prestressing strand sources' ASTM A1081 test results were performed. The results showed that it would take an ASTM A1081 pull-out value of 28,200 lb (125 kN) to have 90% confidence that 95% of beams with single strand would have a transfer length smaller than or equal to the ACI 318-14-calculated transfer length. The results also showed that an ASTM A1081 pull-out value of 14,600 lb (64.9 kN) would have 90% confidenc that 95% of beams containing at least six strands would have a moment capacity greater than or equal to the ACI 318-14-calculated nominal moment capacity.
Keywords: ASTM A1081; Concrete